Implementation of Semi Fowler Position, and Clapping Technique to Increase Oxygen Saturation and Decrease Respiratory Rate (RR) in COPD Patients in ICU Hospital X BSD - Bangun, Dina Mariana; Widani, Ni Luh (Jurnal EduHealth, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is an irreversible condition characterized by shortness of breath during activities and disruption of air flow in and out of the lungs. COPD has the main symptoms, namely shortness of breath, coughing, increased sputum production. One of the non-pharmacological measures for patients with COPD to maintain comfort and facilitate respiratory function is the semi-Fowler position and providing physiotherapy using the clapping technique. The aim of this research is to determine the relationship between giving the semi-Fowler position and the clapping technique to increasing oxygenation. This research method uses a case study of an 85 year old woman, with a diagnosis of COPD who was treated in the ICU, on the 8th day of treatment with a general condition of looking seriously ill, experiencing shortness of breath with RR 30x/minute and Spo2 80%. The semi-Fowler position intervention was carried out at an angle of 30 - 45 degrees for + - 6 hours and the clapping technique was carried out for + - 10 minutes, the clapping technique was carried out in the morning and evening after the nebulizer was applied. There was an effect of increasing oxygen saturation before being given the semi-fowler intervention and giving physiotherapy using the clapping technique, where Spo2 was only 90% but after being given the intervention Spo2 reached 94% - 95%. Thus, giving COPD patients the semi-Fowler position and clapping technique should be given to improve the patient's oxygenation requirements during the treatment period.